Perceptions of Lecturers and Engineering Students of Sophism and Paradox: The Case of Differential Equations - Faezeh Rezvanifard; Farzad Radmehr; Michael Drake (Education Sciences, 2023)
One of the important topics that many STEM (science, technology, engineering, and mathematics) students learn at the tertiary level is differential equations (DEs). Previous studies have explored students’ perceptions of engaging in puzzle tasks in STEM courses; however, no study has explored lecturers’ and students’ perceptions toward using sophism and paradox tasks in teaching mathematics courses, including DEs. This study explores DEs lecturers’ and undergraduate engineering students’ perceptions of using sophism and paradox tasks in the teaching and learning of DEs. The perceptions of 17 lecturers and 134 undergraduate engineering students of sophism and paradox tasks were explored using a questionnaire and semi-structured interviews. The findings showed that more than 50% of lecturers and students perceived that sophism and paradox tasks are enjoyable and entertaining activities which improve students’ mathematical understanding and problem-solving skills, and enhance thinking skills. The findings suggest that sophism and paradox tasks can be used along with routine problems in teaching DEs to provide good opportunities for students to participate more effectively in classroom discussions and motivate them to learn DEs.